Technologies for sustainable forest management: challenges for the 21st century. Commonwealth Forestry Congress, Victoria Falls, Zimbabwe, May 1997 - Sayer, Jeffrey A.; Vanclay, J.K.; Byron, R.N. (Center for International Forestry Research, 1997)
Technology will help to address the challenges for sustainable forestry in the 21st century. Some of the challenges will include the shift of production from native forest to plantations in areas of comparative advantage, more efficient processing delinking end-use products from raw wood characteristics, increased demand, better information technologies to support decision makers, and more options for conserving biodiversity. Definitions of sustainability will vary in time and space as society's expectations and aspirations change, so there can be no "silver bullet" to ensure sustainability. However, progress may be facilitated with a systematic approach to forest management embracing the usual planning cycle: formulation of objectives, preparation of a st rategy, planning, implementing, monitoring, and reappraisal. This requires a good understanding of each particular situation. Managers need good resource assessment and decision support systems; they must foster stakeholder participation in decisions, costs and benefits; and ensure effective procedures to resolve conflicts. Within an appropriate system, technical advances such as better machines and new implements may help to make a difference, but will not in themselves ensure sustainability. The important technologies for sustainable forestry are those that foster better communication between stakeholders and allow informed decisions spanning scales from the gene to the ecosystem. This remains an important challenge for forest managers in their search for sustainability.